2020
DOI: 10.1002/cbin.11465
|View full text |Cite
|
Sign up to set email alerts
|

Current progress in cancer immunotherapy based on natural killer cells

Abstract: One of the most common diseases in the present era is cancer. The common treatment methods used to control cancer include surgery, chemotherapy, and radiotherapy. Despite progress in the treatment of cancers, there still is no definite therapeutic approach. Among the currently proposed strategies, immunotherapy is a new approach that can provide better outcomes compared with existing therapies. Employing natural killer (NK) cells is one of the means of immunotherapy. As innate lymphocytes, NK cells are capable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 121 publications
(180 reference statements)
0
4
0
Order By: Relevance
“…First, the poor ability of NK cells to reach tumor tissues limits their application to the treatment of solid tumors (Melero et al, 2014 ). Second, the tumor microenvironments, including hypoxia, lack of nutrition, and nonappropriate metabolic conditions remain a major barrier to the effectiveness of transferring from NK cells to cancer cells (Bagheri et al, 2021 ). Acidic tumor microenvironments prevent Fas/FasL interactions and decrease perforin/granzyme B release from NK cells (Fischer et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, the poor ability of NK cells to reach tumor tissues limits their application to the treatment of solid tumors (Melero et al, 2014 ). Second, the tumor microenvironments, including hypoxia, lack of nutrition, and nonappropriate metabolic conditions remain a major barrier to the effectiveness of transferring from NK cells to cancer cells (Bagheri et al, 2021 ). Acidic tumor microenvironments prevent Fas/FasL interactions and decrease perforin/granzyme B release from NK cells (Fischer et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Laurent Boissel et al observed that CAR-NK cells exhibited enhanced elimination of primary chronic lymphocytic leukemia (CLL) cells through antibodydependent cell-mediated cytotoxicity (ADCC) mediated by anti-CD20 monoclonal antibodies [71]. iPSC-NK cells engineered with CARs offer several advantages: (1) they have fewer complications such as cytokine release syndrome (CRS), neurotoxicity, or GVHD; (2) they are not restricted by HLA; and (3) they can activate cytotoxic effects independently of the CAR itself [72][73][74][75][76][77]. In a study by Dan Kaufman's group, a first-generation CAR incorporating CD4/CD3ζ was introduced into iPSC-NK cells, demonstrating their ability to suppress human immunodeficiency virus (HIV) replication in CD4 + T cells [68].…”
Section: Translationmentioning
confidence: 99%
“…NK cells are large granular lymphocytes of innate immunity, which do not require thymus for maturation. They play important role in defending the body against viruses naturally, as they do not require any prior exposure (immunologic memory) to that particular viral antigen, hence named “natural” killer cells ( Bagheri et al, 2021 ).…”
Section: General Applicationsmentioning
confidence: 99%